The Role of Employee Wellness Programs in Sustainable Workplace Productivity - Saad Mahdi; Medhat Kadhem Al-Quraishi; Ahmed Fayadh Saleh Hammam; Zainab Jali Madhi; Saad S. Alani; Mykhailo Prygara (Environment and Social Psychology, 2025)
Employee health promotion programs are increasingly gaining attention as a strategic initiative to improve workplace productivity and support employee well-being. This research addresses how such structured wellness programs can affect some organization-wide performance criteria, to include absenteeism reduction, job satisfaction, employee engagement, and stress management at work, workforce retention. A six-month intervention took place in five sectors: health, technology, finance, education and manufacturing, offering the opportunity to compare effectiveness of wellness programs. The results suggest that those service sectors with higher levels of occupational stress (such as health care and manufacturing) experienced proportionately larger decreases in absenteeism and perceived level of stress. In the meantime, industries where there is a dependency on cognitive load (tech/finance) reported the biggest improvement in engagement / job satisfaction. Participation in wellness programs was highly associated with productivity gain, indicating well-being initiatives should be integrated into a company's culture. According to the findings, tailored wellness program strategies, provide employee engagement and retention opportunities that offer long-term value beyond productivity gains. Although positive effects for workplace wellness programs are supported by the research, they should be ongoing to maintain a long-term benefit. Further work should probe the efficacy of digital wellness interventions and compare voluntary versus mandatory participation modalities. The results offer practical implications for organizations interested in developing sustainable well-being interventions aimed to improve not only workforce productivity, but also the overall job satisfaction.